NEXT-FRET maps nonequilibrium rerouting of Escherichia coli maltose-binding protein folding by its signal peptide and chaperones - Chara Sarafoglou; Andreas Kofidis; Marijn de Boer; Mikis Mylonakis; Kostas Mavrakis; Giannis Zacharakis; Yannis Pantazis; Giorgos Gouridis (Proceedings of the National Academy of Sciences, 2026)
Proteins fold through dynamic intermediates that dictate their routes to functional structures, with ensembles predominantly displaying heterogeneity across nanosecond-to-microsecond timescales. Directly observing these states in solution remains challenging as single-molecule methods often require technically demanding microfluidics, surface attachment that alters behavior, or denaturants that distort natural energy landscapes. Here we introduce NEXT-FRET, a solution-based single-molecule platform combining single-molecule FRET (smFRET) with time-varying Gaussian mixture modeling to resolve how diffusing proteins populate and interconvert between conformations under near-native conditions. By incorporating prior equilibrium information into time-dependent analysis, NEXT-FRET requires a few molecules per condition and accessible instrumentation, enabling application in the presence of chaperones and aggregation-prone precursors. We apply NEXT-FRET to the Escherichia coli Maltose-Binding Protein (MBP) and pre-MBP to reveal a long-sought closed on-pathway intermediate that exchanges with both native and unfolded states. The signal peptide raises the barrier selectively for the intermediate-to-native transition. Profiling interactions with chaperones shows that each stabilizes nonnative conformations distinctively, generating kinetic traps. These findings demonstrate that sequence features and proteostasis factors actively reshape the folding landscape. By following molecules out of equilibrium, NEXT-FRET reveals intermediates invisible at equilibrium. This reflects the inherent nonequilibrium character of cells, which maintain order through ongoing energy exchange and dissipation, with fluctuations governing the kinetics and connectivity of biomolecular states. By exposing transient intermediates and quantifying kinetic flows, NEXT-FRET offers a scalable strategy to interrogate nonequilibrium dynamics, providing mechanistic insights into protein (mis)folding, enzyme catalysis, ligand binding and broader biomolecular reactions with implications for biotechnology and therapeutics.